2021
DOI: 10.1128/spectrum.01008-21
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Accuracy of BinaxNOW Rapid Antigen COVID-19 Test in Asymptomatic and Symptomatic Populations in a High-Volume Self-Referred Testing Site

Abstract: The BinaxNOW rapid antigen COVID-19 test had a sensitivity of 87% in symptomatic and 71% asymptomatic individuals when performed by health care workers in a high-throughput setting. The performance may expedite isolation decisions or referrals for time-sensitive monoclonal antibody treatment in communities where timely COVID PCR tests are unavailable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 11 publications
5
24
0
1
Order By: Relevance
“…One such assay, the Abbott BinaxNow, has been recommended for in-home testing and implemented in public health screening campaigns (2)(3)(4)(5)(6). The diagnostic validity of the assay has been demonstrated in laboratory-based and clinical settings, with a sensitivity ranging from approximately 50-90%, depending on disease stage and degree of symptom, and a specificity >99%, compared to laboratory-based PCR assays (3,4,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…One such assay, the Abbott BinaxNow, has been recommended for in-home testing and implemented in public health screening campaigns (2)(3)(4)(5)(6). The diagnostic validity of the assay has been demonstrated in laboratory-based and clinical settings, with a sensitivity ranging from approximately 50-90%, depending on disease stage and degree of symptom, and a specificity >99%, compared to laboratory-based PCR assays (3,4,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…However, with implementation of best practices, similar accuracy would be expected. 12 Our study enrolled only a small number of children with high-risk exposure and the estimates of accuracy had broad confidence interval.…”
Section: Discussionmentioning
confidence: 94%
“…Test implementation, education, and training processes have been previously described. 12 Sample collection. The rapid antigen and RT-PCR samples were collected sequentially for each participant in the study by medical staff who were trained to perform rapid antigen tests.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that antigen testing will miss a proportion of SARS-CoV-2 cases, particularly those with lower viral burden (identified by higher Ct values) particularly among asymptomatic individuals; a recent meta-analysis reported a sensitivity of 58.1% (95% CI 40.2% to 74.1%),(24) and more focused studies including asymptomatic close contacts reported a sensitivity of 59-82% compared to NAT. (25, 26) However, the hope has been that persons with potential to transmit SARS-CoV-2 may be excluded, at least in the moment, by a negative antigen test. (27-29) Used as intended, in the first 5 days of symptom onset, only one patient with culture-positive SARS-CoV-2 tested negative by antigen testing, but two asymptomatic patients who tested negative by antigen tests had positive cultures.…”
Section: Discussionmentioning
confidence: 99%